COVID-19 mRNA Vaccination Generates Greater Immunoglobulin G Levels in Women Compared to Men. (12th June 2021) - Demonbreun, Alexis R; Sancilio, Amelia; Velez, Matt E; Ryan, Daniel T; Pesce, Lorenzo; Saber, Rana; Vaught, Lauren A; Reiser, Nina L; Hsieh, Ryan R; D'Aquila, Richard T; Mustanski, Brian; McDade, Thomas W; et al.
Abstract: We investigated whether the antibody response to coronavirus disease 2019 (COVID-19) mRNA vaccination is similar in women and men. In a community cohort without prior COVID-19, first vaccine dose produced higher immunoglobulin G (IgG) levels and percent inhibition of spike-ACE2 receptor binding, a surrogate measure of virus neutralization, in women compared to men (7.0 µg/mL, 51.6% vs 3.3 µg/mL, 36.4%). After 2 doses, IgG levels remained significantly higher for women (30.4 µg/mL) compared to men (20.6 µg/mL), while percent inhibition was similar (98.4% vs 97.7%). Sex-specific antibody response to mRNA vaccination informs future efforts to understand vaccine protection and side effects.